2018
DOI: 10.3389/fmicb.2018.02315
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of Gut Microbiome in the Patients With Severe Fever With Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by SFTS virus, and the number of SFTS cases increased year by year in China. Previous studies had indicated that gut microbiome closely associated with human health and diseases, including infection diseases, liver diseases, gastrointestinal diseases and metabolic diseases. The aim of this study is to investigate the alterations and involvements of gut microbial in SFTS patients. We compared the gut microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…First, our results showed Lactobacillus and Streptococcus (including S. anginosus, Streptococcus sp., S. parasanguinis , and S. salivarius ) were enriched in ITP patients. The Lactobacillaceae family and its most abundant genus Lactobacillus in ITP patients were significantly higher than in HCs, consistent with the results in patients with severe fever with thrombocytopenia syndrome (SFTS) ( Xu et al, 2018 ). Recent studies revealed regulation of intestinal microbiota in autoimmune arthritis by promoting differentiation and migration of T follicular helper (Tfh) cells ( Block et al, 2016 ; Teng et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…First, our results showed Lactobacillus and Streptococcus (including S. anginosus, Streptococcus sp., S. parasanguinis , and S. salivarius ) were enriched in ITP patients. The Lactobacillaceae family and its most abundant genus Lactobacillus in ITP patients were significantly higher than in HCs, consistent with the results in patients with severe fever with thrombocytopenia syndrome (SFTS) ( Xu et al, 2018 ). Recent studies revealed regulation of intestinal microbiota in autoimmune arthritis by promoting differentiation and migration of T follicular helper (Tfh) cells ( Block et al, 2016 ; Teng et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…A negative correlation between Sutterella and HOMA-IR, and IL-6 contents was found. Sutterella have anti-inflammation properties [ 55 ]. Therefore, the reduction of inflammation by TBF treatment in diabetic mice might be due to the increased abundance of Sutterella , and it was also positively correlated with the decrease in serum IL-6, suggesting that TBF effects on microbiota might be associated with metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcaceae are known opportunistic pathogens, and its typical genus is Streptococcus [50]. Lower abundance of Streptococcaceae and Streptococcus was observed in the dietary BME groups.…”
mentioning
confidence: 97%